Mechanism of liver regeneration: 20-year bibliometric analyses - Jingshu Qi; Yunkai Dai; Xin Sun; Chenghai Liu; Chenghai Liu; Chenghai Liu (Frontiers in Pharmacology, 2023)
Objectives: The study aims to explore the most influential countries, institutions, journals, authors, “research hotspots,” and trends in the study of the mechanism of liver regeneration (MoLR) in the last 20 years using bibliometric analyses.Methods: The literature associated with the MoLR was retrieved from the Web of Science Core Collection on 11 October 2022. CiteSpace 6.1.R6 (64-bit) and VOSviewer 1.6.18 were used for bibliometric analyses.Results: A total of 18,956 authors from 2,900 institutions in 71 countries/regions published 3,563 studies in different academic journals on the MoLR. The United States was the most influential country. The University of Pittsburgh was the institution from which most articles on the MoLR were published. Cunshuan Xu published the most articles on the MoLR, and George K. Michalopoulos was the most frequently co-cited author. Hepatology was the journal in which most articles on the MoLR were published and the most frequently co-cited journal in this field. The research hotspots for the MoLR were origin and subsets of hepatocytes during LR; new factors and pathways in LR regulation; cell therapy for LR; interactions between liver cells in LR; mechanism of the proliferation of residual hepatocytes and trans-differentiation between cells; and prognosis of LR. The emerging topic was the mechanism of regeneration of a severely injured liver.Conclusion: Our bibliometric analyses provide (i) a comprehensive overview of the MoLR; (ii) important clues and ideas for scholars in this field.